Strategi Visual Branding Produk Intangible pada Konten Feed Instagram @peruri.digital - Hafidz, Mahesa Al; Suyanto, Budi; Hasian, Irene (Lembaga Teewan Journal Solutions, 2026)
Public trust in digital products cannot be established through physical experience, making visual representation the primary medium through which trust signals are constructed and communicated to audiences. This study examines the visual branding strategy of @peruri.digital Instagram feed content in constructing visual trust signals for Peruri Digital’s intangible products using a qualitative single-case study approach. Data were obtained through triangulation of three sources: visual content analysis of six feed posts published between March and July 2025, in-depth interviews with the design mentor, and analysis of the company’s official brand guidelines. The analysis integrates Wheeler’s (2017) visual identity framework, Lakoff & Johnson’s (2003) conceptual metaphor theory, and Harris and Goode’s (2010) e-servicescape theory as complementary analytical frameworks. The findings identify three integrated mechanisms: corporate color consistency as an identity anchor, familiarization metaphors that translate product abstraction through physical experiences familiar to audiences, and a flexible brand consistency strategy that preserves core brand identity while adapting communication to platform characteristics. All deviations from the official brand guidelines were found to reflect coordinated adaptation decisions in Peruri Digital’s visual branding implementation.